2013
DOI: 10.1111/pan.12139
|View full text |Cite
|
Sign up to set email alerts
|

Plethysmographic Variability Index (PVI) accuracy in predicting fluid responsiveness in anesthetized children

Abstract: This study found both PVI and prechallenge SVI to be accurate when used to predict fluid load response during anesthetized noncardiac surgery in children. However, a third of recorded PVI values were inconclusive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 43 publications
2
25
0
Order By: Relevance
“…Data recorded in the adult population suggest that PVI predicts fluid responsiveness [14]. Similarly, encouraging data has emerged in the pediatric population as well [15][16][17]. In the present study, there were no significant changes in the PVI following phlebotomy when the cohort was analyzed as a whole.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Data recorded in the adult population suggest that PVI predicts fluid responsiveness [14]. Similarly, encouraging data has emerged in the pediatric population as well [15][16][17]. In the present study, there were no significant changes in the PVI following phlebotomy when the cohort was analyzed as a whole.…”
Section: Discussionsupporting
confidence: 61%
“…Another measure of plethysmography variation has been developed and incorporated into a new generation of pulse oximetry (Radical 7 pulse oximeter, Masimo Corporation, Irvine CA) and deemed the pleth variability index (PVI). A recent meta-analysis in adults [14], and three recent pediatric studies have shown PVI to accurately predict fluid responsiveness [15][16][17].…”
Section: B Schloss Et Al / Plethysmography Variability Index Duringmentioning
confidence: 99%
“…By contrast, the Doppler peak velocity of descending aortal blood flow was noted as being less predictive of fluid responsiveness in critically ill children . In addition, a systematic analysis of 12 studies found that both PPV and SVV failed to predict fluid responsiveness, and the prediction value of PVI was inconclusive . These findings indicate that respiratory cyclic changes in hemodynamics are less reliably detectable in the peripheral circulation of the pediatric population because children have more compliant arteries and a more compliant thorax .…”
Section: Discussionmentioning
confidence: 94%
“…In all original publications included in this systematic review, the authors proposed a single cutoff point for DVPeak to make a clinical discrimination between responders and nonresponders to fluid challenge. Nevertheless, recent studies suggest that this threshold value, determined using a classic ROC curve approach, does not allow certainty in the determination of fluid-responsive status due to the existence of an inconclusive 'gray zone' that has been identified for several dynamic parameters of fluid responsiveness in adults and children (41)(42)(43)(44). We believe that it would be of great interest to specifically define the gray zone of DVPeak for mechanically ventilated children in the operating room.…”
Section: Discussionmentioning
confidence: 99%